Seismological research in Yunnan Province, China, and its tectonic implication between the Xianshuihe-Xiaojiang fault system and the Red River fault zone - Dong, Shaopeng; Han, Zhujun; Guo, Peng; Xie, Zhangdi; Yin, Xinzhong (Frontiers in Earth Science, 2023)
The tectonic crosscutting relationship between Xianshuihe-Xiaojiang fault system(XFS) and the Red River fault zone(RRF) is the key basic problem, but still in hot argument, in geodynamic model of southeast margin of Tibetan Plateau. In order to answer whether XFS has cut across RRF and extended southwardly, multiple seismological methods, including seismic relocation, b-value analysis, seismic energy, density study, focal mechanism inversion and regional stress field research, were applied in Yunnan Province area, China. The results comprehensively demonstrate southern segment of the XFS has not been affected by the RRF, and it has continued for a length after crossing the RRF. But Dian Bien Phu fault zone is not an extension fault of XFS. Along the NE direction, starting from the middle segment of XFS, and cutting across Qujiang fault, Shiping-Jianshui fault zone, RRF, Ailaoshan fault zone, Wuliangshan fault zone and the southern section of Daluo fault, the belt should be treated as the eastern boundary of the clockwise rotational geodynamics model of the Tibetan Plateau in this study area. Based on these conclusions above, a new geodynamic evolution model is proposed.